(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2021)
The study has attempted to explore the relationship between disability and job satisfaction among employees with chronic illnesses and disability in the Indian organizations (Delhi NCR, India). The direct correlation statistic for disability and job satisfaction was weak and negative. To explore the relationship further, the role of industry wise differences and size of the organizations (based on number of employees) in the relationship of the disability and job satisfaction among this group was examined using hierarchical regression analysis. The results suggest strong moderation effect of industry sector of the organization in the relationship between disability and job satisfaction of employees with chronic illness and disability.